Effect of Remote Ischemic Conditioning in Patients With Takotsubo Syndrome After Acute Stroke: Study Protocol for a Randomized Controlled Trial - Wang, Tao; Xu, Yueqiao; Wang, Ning; Qi, Meng; Cheng, Weitao; Qu, Xin (Frontiers in Neurology, 2020)
Introduction Takotsubo syndrome (TTS) is an acute heart failure syndrome which is preceded by a variety of emotional or physical triggers, with central nervous system conditions being an important trigger. Remote ischemic conditioning (RIC) is a promising interventional treatment, based on the probability that both TTS and acute coronary syndrome may respond similarly to interventions. The heart protection effect of RIC has been repeatedly confirmed in animal models and observational clinical trials; however, it has never been studied in patients with TTS after acute stroke in randomized clinical trials with a higher level of evidence. The present study will be a proof-of-concept study to determine whether RIC can reduce cardiac injury and eventually improve the heart function and clinical outcomes of TTS patients after acute stroke. Methods and analysis A single-centre, outcome-assessor-blinded, randomized controlled trial (RCT) will be conducted to evaluate the effect of RIC in TTS patients after acute stroke. Major eligibility criteria include TTS patients diagnosed with acute stroke, which can be confirmed on computed tomography or magnetic resonance imaging; patients aged 18 to 75 years; patients admitted to a hospital within 48 hours after the onset of acute stroke; and patients are diagnosed with Takotsubo cardiomyopathy with an InterTAK diagnostic score ≥ 50. A total of 60 eligible patients will be randomly allocated into either the RIC or control groups. The primary endpoint is a composite of death from any cause and major adverse cardiac and cerebrovascular events during in-hospital period, and at the 1- and 6-month follow-up. Ethics and dissemination This study has been approved by the Medical Ethics Committee of Xuanwu Hospital, Capital Medical University ([2017] 072), and the study findings will be presented at international conferences and published in a peer-reviewed journal. Trial registration This study has been prospectively registered in the Chinese Clinical Trial Registry on September 10, 2018 (ChiCTR1800018290).